Approaches to Research Methodology of Ethnic Stereotypes (with the Example of the Image of the Estonian in the View of Russian-speaking Students of Estonia): К вопросу о методологии исследования этнических стереотипов (на примере изучения образа эстонца в представлении русскоязычной студенческой молодежи Эстонии) - Burdakova, Olga; Nõmm, Jelena (Przegląd Wschodnioeuropejski, 2021)
Ethno-cultural stereotypes are the result of comparing one´s own culture, customs, traditions with that of strangers, identifying and fixing differences between the cultures of ethnic groups. Stereotypical images of different peoples exist even in the minds of those people who had no experience in communication with representatives of these ethnic groups. However, the results of the study of ethnic stereotypes of people who are in direct contact with this ethnic group and see it up close in comparison to people who evaluate it from a distance, often raises more questions than gives clear answers. The solution of these questions raises before the researcher a whole complex of methodological problems. The article will introduce a new methodological approach to reveal ethno-cultural stereotypes in the text culture and in our contemporaries’ common sense perception. To distinguish between people’s individual perception of a particular ethnos and collective stereotypes, the following qualitative and quantitative criteria are suggested: 1) bipolar orthonormal core axes of parameter distribution; 2) the significance of the axis; 3) the degree of consistency of parameters distributed on the axis; 4) the weighting coefficient of testee’s reaction.